Bendless is essential for PINK1-Park mediated Mitofusin degradation under mitochondrial stress caused by loss of LRPPRC. - Rajit Narayanan Cheramangalam; Tarana Anand; Priyanka Pandey; Deepa Balasubramanian; Reshmi Varghese; Neha Singhal; Sonal Nagarkar Jaiswal; Manish Jaiswal (PLoS Genetics)
Cells under mitochondrial stress often co-opt mechanisms to maintain energy homeostasis, mitochondrial quality control and cell survival. A mechanistic understanding of such responses is crucial for further insight into mitochondrial biology and diseases. Through an unbiased genetic screen in Drosophila, we identify that mutations in lrpprc2, a homolog of the human LRPPRC gene that is linked to the French-Canadian Leigh syndrome, result in PINK1-Park activation. While the PINK1-Park pathway is well known to induce mitophagy, we show that PINK1-Park regulates mitochondrial dynamics by inducing the degradation of the mitochondrial fusion protein Mitofusin/Marf in lrpprc2 mutants. In our genetic screen, we also discover that Bendless, a K63-linked E2 conjugase, is a regulator of Marf, as loss of bendless results in increased Marf levels. We show that Bendless is required for PINK1 stability, and subsequently for PINK1-Park mediated Marf degradation under physiological conditions, and in response to mitochondrial stress as seen in lrpprc2. Additionally, we show that loss of bendless in lrpprc2 mutant eyes results in photoreceptor degeneration, indicating a neuroprotective role for Bendless-PINK1-Park mediated Marf degradation. Based on our observations, we propose that certain forms of mitochondrial stress activate Bendless-PINK1-Park to limit mitochondrial fusion, which is a cell-protective response.